MEMBANGUN CITY BRANDING MELALUI SOLO BATIK CARNIVAL - Murfianti, Fitri (Institut Seni Indoensia Surakarta, 2010)
City branding is an ejfort to establish the identity of a city. ldentiql is a construction. a consequence of BÂ process of interaction between people, institutions, and praxis in social life; o place/region which bring:its uniqueness and may appear diï¬erently from its competitors not only in slogans or tagline but also in itsÂ ability to oï¬er something which is unique and dtï¬‚erenl, crystallized as a strong identity in the customersâ€˜Â perception. Solo Batik Carnival is a creative industry that produces â€œsymbolic goods â€ in the form of ideas,Â experiences, and images. The event is hold as on effort to construct the image which represents the city ofÂ Solo as a city of Batik and makes the city of Solo a marketable city. Thus, SBC has a dual function. Apanfrom an attempt to potent batik culturally and oï¬‚irm brand Solo as the City of Batik, SBC also can functionÂ as a showroom or storefront that oï¬‚ers a unique batik Solo as a unique selling proposition so that it can beÂ used as a tourism pmmotion event of the city of SoloÂ in national and international scale.Keywords: Solo Batik Carnival, City Branding, Identity